Overexpression of GLT1D1 induces immunosuppression through glycosylation of PD‐L1 and predicts poor prognosis in B‐cell lymphoma. Issue 5 (13th April 2020) - Liu, Xiaoxia; Zhang, Yanyu; Han, Yi; Lu, Wenhua; Yang, Jing; Tian, Jingyu; Sun, Peng; Yu, Tiantian; Hu, Yumin; Zhang, Hui; Huang, Peng; Liu, Panpan
Abstract : B‐cell non‐Hodgkin's lymphoma (NHL) is a class of heterogeneous diseases with variable clinical outcomes. Immunosuppression is particularly common in the subtypes of lymphoma with poor prognosis, but the underlying mechanism remains unclear. Using a RT‐PCR array analysis, we have identified that glycosyltransferase 1 domain‐containing 1 (GLT1D1), an enzyme that transfers glycosyl groups to proteins, is highly upregulated in the incurable subtype of B‐cell NHL and in early relapse diffuse large B‐cell lymphoma. Analysis of clinical specimens revealed that GLT1D1 expression was positively correlated with the level of glycosylated programmed cell death‐ligand 1 (PD‐L1) in B‐cell NHL and that high GLT1D1 expression was associated with poor prognosis. Mechanistically, we showed that GLT1D1 transferred N‐linked glycans to PD‐L1, thus promoting the immunosuppressive function of glycosylated PD‐L1. Downregulation of GLT1D1 resulted in a decrease of glycosylated PD‐L1 and enhanced cytotoxic T‐cell function against lymphoma cells. In vivo, overexpression of GLT1D1 promoted tumor growth by facilitating tumor immune escape through increased levels of PD‐L1. Our work has identified GLT1D1 as a predictive biomarker for B‐cell NHL. It has also shown that this enzyme enhances PD‐L1 stabilization via N‐glycosylation, thus promoting immunosuppression and tumor growth. As such, GLT1D1 might be a novel therapeutic target for the treatment of B‐NHL. Abstract : B‐cell non‐Hodgkin's lymphoma (B‐NHL) is a heterogeneous group of diseases with different biological characteristics and clinical outcomes. The expression of glycosyltransferase 1 domain‐containing 1 (GLT1D1) in B‐NHL was positively correlated with the level of glycosylated PD‐L1, and high GLT1D1 expression was associated with poor prognosis. GLT1D1 transferred N‐glycans to the asparagine residue of PD‐L1 and thus enhances its stability, leading to immunosuppression and poor clinical outcome.